In-vitro Callus Induction of Durian (Durio zibethinus Murr.) Leaves Using Kinetin and 2,4-D (Dichlorophenoxyacetic acid) - Handayani, Rd. Selvy; Yunus, Ismadi; Sayuti, M.; Irawan, Endri (Yayasan Pertanian Tropika Indonesia (YPTI), 2019)
Durian (Durio zibethinus Murr.) is a tropical fruit grown in Southeast Asia and it has high nutritional and economic values and highly appreciated by consumers in Indonesia. Unfortunately, there are several obstacles in planting durian in Indonesia, specifically in Aceh. One of the abstacles is the scarcity of superior durian plants. Generally, plant conservations done conventionally through vegetative propagation. However, this technique has disadvantage such as harming the initial plants. Therefore, plant culture tissue has been used as a modern technique to develop durian plants. The objective of this research was to evaluate the effect of kinetin and 2,4 D on development of durian leaf explants through in-vitro bioassay. The research was conducted at Tissue Culture Laboratory, Faculty of Agriculture, Malikussaleh University from January to April 2019 using Completely Randomized Design (CRD) Factorial with 2 factors observed. The first factor was Kinetin (K): 0.0, 0.1 and 0.5 ppm. The second factor was auxin 2,4 D: 0.0, 0.5 and 1.0 ppm. The results showed that the in-vitro application of kinetin affected the induction of leaf callus. The application of 0.5 ppm of kinetin gave the best result compared to others. The in-vitro application of 2,4 D 0.5 ppm also possessed the best result compared to others. There was no interaction beween in-vitro application of kinetin and 2,4 D on the growth of durian leaf callus at all parameters observed.